Hegemoni Amerika Dalam Film Independence Day: Resurgence - Rina Darojatun (Wardah, 2023)
The United States uses Hollywood as a mecca for the world's entertainment industry to instill its ideology in ruling and controlling other countries through films. This article discusses films that can hypnotize audiences and are the product of a socio-political and cultural structure, one of the films entitled Independence Day: Resurgence is inserted by hegemonic practices by instilling ideology in the audiences who watch it. This study aims to explain how the hegemony of the United States in the world through a content analysis approach that is reviewed by media dependency theory and Marxist media theory, data collection techniques by looking at the text in the film and the context behind it. In conclusion, the theory of media dependency analyzing the influence of the media is able to create new cognitions for the reputation of society and the state so that it can easily instill its influence, doctrine and global hegemony. This is evidenced by the film's theme, namely the historic day of "independence day" of the United States. This is where the momentum is to be used as a venue for "proofing" them or the big countries' Self Assertion. Through a Marxist media theory approach, in fact the United States wants to show a friendly face to all countries while maintaining its image as the ruling state and world police. The United States consciously applies the established status quo as a superpower. The scientific argument that is built is that the specific political-economic conditions that develop in a country, have a mutually determining relationship influenced by global political-economic conditions.